Aneurisma de la arteria renal causando hipertensión arterial. Reporte de un caso. - Blanco Rabassa, Eladio; Portilla Sánchez, Ricardo; Blanco Molina, José; Rodríguez Menéndez, Gustavo (Revista Cubana de Pediatría, 2023)
Reporte de un caso.